Neuroendocrine Differentiation in Non-Small Cell Lung Cancer and its Relation to Different Pathologic Features: An Immunohistochemical Study - El-Hussien, Mahmoud Tag; Hassan, Mohamed Abdelfattah (Asian Pacific Journal of Cancer Biology, 2021)
Objectives: To identify the relevance of neuroendocrine differentiation in non-small cell lung cancer and its correlation with different pathological features. Materials and Methods: A total number of 30 cases of per cutaneous CT guided biopsies of primary non-small lung cancer were collected in the pathology department of Misr University for Science and Technology Giza, Egypt and private practice in the time period from January 2018 till December 2020. Immunohistochemical study for neuroendocrine differentiation was performed using mono clonal antibodies against synaptophysin, chromogranin A and CD56. For all selected cases, clinical and pathological data such as age, gender, histologic types, grade and clinical stage were collected, tabulated and statistically analyzed with the results of neuroendocrine markers expression. Cases with incomplete pathological data and cases with histologic picture of neuroendocrine differentiation were excluded. Results: A total number of 30 cases of primary non-small lung cancer were enrolled in this study. The median age of patients was 61.5 years. There were 21 (70%) males and 9 (30%) females. Regarding neuroendocrine markers, positivity for either marker was identified in 23.3% of non-small cell lung cancer. Chromogranin A was positively expressed in 9 (30%) of cases, synaptophysin was positively expressed in 7 (23.3%) of cases and CD56 was positively expressed in 5 (16.7%) of cases. Only 2 cases (6.7%) showed co-expression of two markers. It was found that there was a high significant relation between chromogranin A expression and clinical stage. Chromogranin A expression was significantly higher in stage III than stage I and II (P<0.001). There was no statistical significant difference between synaptophysin, chromogranin A and CD56 expressions and the rest of the studied pathologic data. Conclusion: A considerable number of non-small cell lung cancer has neuroendocrine differentiation for at least one neuroendocrine marker despite absence of morphologic features. Much less number of cases showed expression of two markers. A reasonable panel of neuroendocrine markers is recommended to detect this differentiation which may have a clinical impact and optimize an alternative therapeutic option.